Hubungan Aktivitas Fisik Saat Pandemi Covid-19 dengan Tingkat Nyeri Dismenore Primer - Leviany Aulia; Yosi Maria Wijaya; Asri Endah Nuratri (Universitas Faletehan, 2022)
This research was triggered by complaints of female students who suffered from dysmenorrhea and had their activities disturbed. Meanwhile, dysmenorrhea symptoms can be overcome by physical exercises, pharmacological and non-pharmacological therapies. Lack of exercises is a risk factor of dysmenorrhea pain severity. Moreover during Covid-19 pandemic, exercises became one of the top physical activities for maintaining immunity and physical health. The purpose of this study was to determine the correlation between physical activities during Covid-19 pandemic and dysmenorrhea pain levels among female students. This study used cross-sectional approach and the data collection technique used International Physical Activity Questionnaire Short Form (IPAQ-SF) instrument. The sampling method used purposive sampling and the sample size were 194 respondents. The results of Spearman's rank statistical test showed a correlation between physical activities during Covid-19 pandemic and the pain level of primary dysmenorrhea, in which the r value is 0.745 and the p-value is <0.05. The Research results could be disseminated to educational institutions to carry out a program of joint physical activity.